Titanium Mesh Reconstruction after Solitary Sternal Plasmacytoma Surgery-A Case report - Krdzalic G; Mujagic H; Musanovic N; Krdzalic A (International Journal of Immunotherapy and Cancer Research - Peertechz Publications, 2017)
We present chest wall reconstruction with titanium mesh in a patient who underwent sternal resection due to solitary plasmacytoma (SP). A 35 year old female was admitted to The Thoracic Surgery Department of University Clinical Center Tuzla with pain and tender upper-sternal swelling. Thoracic magnetic resonance imaging (MRI) revealed hypo dense wll-shaped rounded mass involving manubrium streni which was 40mmx40mm in size measured by two right angle perpendicular diameters. Affected part was resected together with removal of sternoclavicular and costochondral junctions and reconstruction with titanium mesh was performed.